2014
DOI: 10.1109/mcg.2014.82
|View full text |Cite
|
Sign up to set email alerts
|

Visualization beyond the Desktop--the Next Big Thing

Abstract: Visualization is coming of age. With visual depictions being seamlessly integrated into documents, and data visualization techniques being used to understand increasingly large and complex datasets, the term "visualization"' is becoming used in everyday conversations. But we are on a cusp; visualization researchers need to develop and adapt to today's new devices and tomorrow's technology. Today, people interact with visual depictions through a mouse. Tomorrow, they'll be touching, swiping, grasping, feeling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 18 publications
(14 reference statements)
0
54
0
Order By: Relevance
“…Our work is an extension of Andromeda [50] for visual analytics beyond the desktop [51]. The desktop-based application has several educational limitations for learners who have not experienced data analytics yet.…”
Section: Teach High Dimensional Data Using Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work is an extension of Andromeda [50] for visual analytics beyond the desktop [51]. The desktop-based application has several educational limitations for learners who have not experienced data analytics yet.…”
Section: Teach High Dimensional Data Using Visualizationmentioning
confidence: 99%
“…In our everyday life, we are heavily accustomed to processing information integrated from vision, hearing, touching, moving, and etc. It is desirable to exploit the same approach to interact with data [51]. Here, we took a more proactive approach to employ our own bodies as movable data points so that we are able to map data analysis to an integrated sensory/motor activity, not just to visual.…”
Section: Teach High Dimensional Data Using Visualizationmentioning
confidence: 99%
“…Visualization has been developing since Ivan Sutherland had introduced sketchpad (robot draftsman) in 1963 to show that computer graphics could be used for both artistic and technical purpose [34].…”
Section: Visualizationmentioning
confidence: 99%
“…Visualization algorithms have been designed by engineers and researchers to map the data into a visual form or structure; bar charts, scatter plots, line graphs and many more [34]. In [40] found that most of visualization sources in scientific publications are diagrams, graphs, charts, plots, flowcharts, timelines and tables.…”
Section: Visualizationmentioning
confidence: 99%
“…Roberts and Walker [2010] encouraged the InfoVis community to develop a unified theory that covers all human senses and allows the integration of multiple modalities. They further foresee visualizations beyond the desktop, which use different modalities to both perceive and interact with information as "the next big thing" [Roberts et al, 2014]. Data representa- Figure 4.14: Examples of physicalizations using multiple modalities.…”
Section: Examples For Physicalizationsmentioning
confidence: 99%